Safety and efficacy of dabigatran versus warfarin in patients undergoing catheter ablation of atrial fibrillation: a systematic review and meta-analysis. Issue 4 (22nd July 2013) - Providência, Rui; Albenque, Jean-Paul; Combes, Stephane; Bouzeman, Abdeslam; Casteigt, Benjamin; Combes, Nicolas; Narayanan, Kumar; Marijon, Eloi; Boveda, Serge
Abstract : Background: Dabigatran etexilate, a new thrombin inhibitor, has been shown to be comparable to warfarin in patients with atrial fibrillation (AF). However, there is a limited body of evidence on the efficacy and safety of using dabigatran among patients undergoing AF catheter ablation. Objective: A random effects meta-analysis was performed of controlled trials comparing dabigatran and warfarin in paroxysmal/persistent AF patients undergoing catheter ablation. Methods: Data sources included Medline, Embase, and Cochrane (from inception to April 2013). Three independent reviewers selected studies comparing warfarin to dabigatran. Descriptive and quantitative information was extracted from each selected study, regarding periprocedural all cause mortality, thromboembolic events and major bleeding, as well as modalities of periprocedural anticoagulation bridging. Results: After a detailed screening of 228 search results, 14 studies were identified enrolling a total of 4782 patients (1823 treated with dabigatran and 2959 with warfarin). No deaths were reported. No significant differences were found between patients treated with dabigatran and warfarin as regards thromboembolic events (0.55% dabigatran vs 0.17% warfarin; risk ratios (RR)=1.78, 95% CI 0.66 to 4.80; p=0.26) and major bleeding (1.48% dabigatran vs 1.35% warfarin; RR=1.07, 95% CI 0.51 to 2.26; p=0.86). No difference was found between the 110 mg twice daily and 150 mg twice daily dabigatran dosages concerning major bleeding (0% vs 1.62%, respectively; RR=0.19, 95% CI 0.01 to 3.18; p=0.25) and thromboembolism (0% vs 0.40%, respectively; RR=0.72, 95% CI 0.04 to 12.98; p=0.82). Conclusions: In the specific setting of AF catheter ablation, this first pooled analysis suggests that patients treated with dabigatran have a similar incidence of thromboembolic events and major bleeding compared to warfarin, with low event rates overall.